Análise dos efeitos argumentativos das parábolas de Jesus Cristo: Uma pesquisa à luz da metáfora - SILVA, Ivânia Oliveira Dias e (2022)
This work, inserted in the theoretical assumptions of Cognitive Linguistics and linked to Discourse Analysis, aims to analyze the argumentative effects present in the parables of Jesus Christ, from the perspective of the Theory of Conceptual Metaphors. For this, initially, we seek to understand some particularities about the genre, as well as the concepts given by some authors who investigate this theme. Then, based on Bakhtin (1997), the characteristics given by the author to the various linguistic manifestations are verified, to qualify the parable as a discursive genre. During this study, are used as corpus, namely: the parable of the lost sheep, the parable of the lost coin and the parable of the lost son. This is qualitative research, of a descriptive-exploratory nature. It is also bibliographical and documentary. The question that guided the research concerns the metaphorical language present in the parables of Jesus and its contribution as a strategy to convince and/or persuade the audience. For that, we worked with the hypothesis that the argumentativeness present in the parables of Jesus is related to cognition and understanding of the message, through the emergence and negotiation of meanings through figurative language. The bibliographic review is based on texts that deal with the metaphor approach and the expansion of its concept about its multidisciplinarity. Due to coverage in several domains of knowledge, Vereza (2007; 2010; 2013; 2016) contributes to the study of metaphor in language in use, and the conciliation between cognition and discourse. This new prism determines a given argumentative orientation, and it is from discursive unfoldings or mappings that they play a role, both cognitive and argumentative, whose discursive chaining takes place through “metaphorical niches”. Through Amossy (2017; 2018), foundations were sought for the concrete study of argumentative discourse, so that, theoretically- methodologically, it instrumentalizes it. The focus given to the study of parables was given through: Bailey (1985), Jeremiah (1986), Kunz (2014) e Sant'Anna (2010). The research demonstrates the relevance of the study, highlighting the effects of argumentation and metaphor in the selected parables, and contributing with significant data for future works that will deal with this theme, in addition to encouraging the development of other investigations in this area.